New Threats and Methods of Protection of Financial Services in the Mobile Banking Sector - Sobiesiak, Magdalena; Zagrodniczek, Paweł (Journal of Finance and Financial Law, 2018)
The purpose of this article is to examine consumer awareness in the use of mobile banking in Poland. The evolution of mobile banking as well as the scale of its occurrence are also presented. The study presents the results of a survey conducted in the form of a survey, the level of knowledge and typical habits when using m-banking for students of Lublin universities. In addition, examples of cybercriminals' methods of operation based on information presented by selected banks and financial sector institutions are discussed.